(3bUU GdCfHjGAs - (3CHh YHO Gddg eMeO Hf SYjO Hf gTGe GdMLQjs
(3ChdgG (B:s
(3Chdg HYO GdHSedI (B: (3bGd MOKfG CHh eMeO YHO Gdedc Hf gTGe Yf CHj EOQjS GdNhdGfi , Yf LOg dCeg hgH Hf efHg GdjeGfi Cfg bGd (B: (3bQCJ EKfjf hSHYjf cJGHkG ef GdcJH GdefRdI Ydi CfHjGFg s
(3BNQgG (B:s
(3jfJgi HNHQ GdJehQO s
(3Yf CHj YHO Gddg Hf efHg GdjeGfi GdeJhai SfI (B110(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B117 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs